Seasonal and diurnal trends in progressive isotope enrichment along needles in two pine species. (27th October 2020) - Kannenberg, Steven A.; Fiorella, Richard P.; Anderegg, William R. L.; Monson, Russell K.; Ehleringer, James R.
Abstract: The Craig–Gordon type (C–G) leaf water isotope enrichment models assume a homogeneous distribution of enriched water across the leaf surface, despite observations that Δ 18 O can become increasingly enriched from leaf base to tip. Datasets of this 'progressive isotope enrichment' are limited, precluding a comprehensive understanding of (a) the magnitude and variability of progressive isotope enrichment, and (b) how progressive enrichment impacts the accuracy of C–G leaf water model predictions. Here, we present observations of progressive enrichment in two conifer species that capture seasonal and diurnal variability in environmental conditions. We further examine which leaf water isotope models best capture the influence of progressive enrichment on bulk needle water Δ 18 O. Observed progressive enrichment was large and equal in magnitude across both species. The magnitude of this effect fluctuated seasonally in concert with vapour pressure deficit, but was static in the face of diurnal cycles in meteorological conditions. Despite large progressive enrichment, three variants of the C–G model reasonably successfully predicted bulk needle Δ 18 O. Our results thus suggest that the presence of progressive enrichment does not impact the predictive success of C–G models, and instead yields new insight regarding the physiological and anatomical mechanisms that cause progressive isotope enrichment. Abstract : Δ 18 O of needle water in two conifer species was drastically enriched down the length of the needle, the magnitude of which was driven by seasonal increases in VPD. Despite this progressive enrichment, traditional Craig‐Gordon model variants successfully predicted bulk needle water Δ 18 O.